MUNAWIR SJADZALI AND THOUGHT - Mujiburrahman Mujiburrahman (SHIBGHAH: Journal of Muslim Societies, 2020)
Munawir Sjadzali is known in Indonesia as Minister of Religion of the Republic of Indonesia for two periods (1983-1988 and 1988-1993). Munawir Sjadzali is not only famous for his breakthroughs in government, but also consistent with his thoughts. This is what attracts reviewers of his thought to continue to explore who is Munawir Sjadzali? What are the characteristics of his thoughts, so that the results of his thoughts shake the scientific treasures in Indonesia? At a glance, from the educational aspect, he has made good changes by increasing human resources. Meanwhile, from the aspects of Islam and State Administration, he tends to follow the third stream, a school that on the one hand rejects the notion that Islam contains everything. Likewise, with the issue of bank interest and inheritance, he referred to the spirit of the experience of the caliph Umar bin Khattab. Regarding Munawir's thoughts on the issue of inheritance 2: 2, according to him, this can be accepted because women and men are equal before Allah. What is different is piety and faith.